2004
DOI: 10.1086/420876
|View full text |Cite
|
Sign up to set email alerts
|

Deep Near‐Infrared Observations of the W3 Main Star‐forming Region

Abstract: We present a deep JHK s -band imaging survey of the W3 Main star-forming region, using the near-infrared camera SIRIUS mounted on the University of Hawaii 2.2 m telescope. The near-infrared survey covers an area of $24 arcmin 2 with 10 limiting magnitudes of $19.0, 18.1, and 17.3 in the J, H, and K s bands, respectively. We construct JHK color-color and J versus JÀH and K versus HÀK color-magnitude diagrams to identify young stellar objects and estimate their masses. Based on these color-color and color-magnit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
94
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(105 citation statements)
references
References 38 publications
11
94
0
Order By: Relevance
“…Thus, d(logλF λ )/d(logλ) > 0 between 1 and 10 μm, which is consistent with the classification of VLA 8A as a Class I source (e.g., Hartmann 1998). Regarding the near-infrared colors of the 2MASS sources associated with IRS 1 and VLA 8A, derived from 2MASS photometry (see Table 13), we found that both sources fall inside the area corresponding to YSOs of Class 0/I (e.g., Itoh et al 1996;Ojha et al 2004;Matsuyanagi et al 2006). Finally, VLA 8B, which is also associated with dense gas tracers, shows no infrared emission at all.…”
Section: Discussionsupporting
confidence: 86%
“…Thus, d(logλF λ )/d(logλ) > 0 between 1 and 10 μm, which is consistent with the classification of VLA 8A as a Class I source (e.g., Hartmann 1998). Regarding the near-infrared colors of the 2MASS sources associated with IRS 1 and VLA 8A, derived from 2MASS photometry (see Table 13), we found that both sources fall inside the area corresponding to YSOs of Class 0/I (e.g., Itoh et al 1996;Ojha et al 2004;Matsuyanagi et al 2006). Finally, VLA 8B, which is also associated with dense gas tracers, shows no infrared emission at all.…”
Section: Discussionsupporting
confidence: 86%
“…We adopt a distance range from 1.4 -1.8 kpc. We estimate the extinction by de-reddening the stars using the JHK colour-colour plot (Kumar, Ojha & Davis 2003;Ojha et al 2004). This is done by shifting them along the reddening vector to a line drawn tangential to the turn-off point of the main sequence locus (Tej et al 2006).…”
Section: Spectral Energy Distribution Of Selected Ysosmentioning
confidence: 99%
“…These stars are located between the upper and middle reddening vectors in the near-IR CC diagram and they are considered to be either field stars or weak-line T Tauri stars (WTTSs)/Class III sources with no or small near-IR excess. However, it is very difficult to distinguish between WTTSs with small near-IR excess and field stars from only near-IR CC diagram (Ojha et al 2004). The near-IR emission of 'T' region stars arise from both photosphere and circumstellar disc ( Lada & Adams 1992).…”
Section: Ysos From Near-ir Colour-colour Diagrammentioning
confidence: 99%
“…In conjugation with deep optical photometric data the identified PMS can be better characterized (e.g., mass, age) by comparing their positions on the HR digram with the theoretical evolutionary models. The characterization PMS stars are essential to derive the cluster properties and to understand its star formation history (e.g., Lada & Lada 1991;Persi et al 1994;Tapia et al 1997;Ojha et al 2004). We therefore studied the cluster with multiwavelength photometric data to have a better picture on the cluster properties and star formation activity.…”
Section: Introductionmentioning
confidence: 99%